Challenges in Cloud Computing Adoption for SMEs in the Middle East - Fatma, Abudaqqa (European Scientific Journal, ESJ, 2024)
Technology’s growth significantly affects how businesses grow because it offers new ways to do business. Due to a sharp rise in market competition and a rapidly changing business environment, businesses in all industries and sectors utilize information and communication technologies (ICTs) to enhance their company operations and boost their value. This study looks at the challenges that small and medium-sized businesses in Middle Eastern nations face when implementing cloud computing. The inclusion and exclusion criteria, as well as the analytic procedure, were documented in the study using the PRISMA protocol. The study also looked for pertinent journal publications that employed mixed, qualitative, and quantitative research methodologies using three pertinent databases: Sustainability, Google Scholar, and Emerald. The included English-language publications had to have been released between the first quarter of 2023 and 2016. More significantly, the evaluation did not include any research that did not concentrate on SMEs in the Middle East. Following an extensive analysis of the literature, it was discovered, among other things that infra needs to be more, budgetary restrictions, and a need for increased understanding of the significance of Industry 4.0. Additionally, Industry 4.0 is the integration of intelligent digital technologies into manufacturing and industrial processes. Suggestions for solutions to the noted obstacles were also made.